Transfer Student Engagement: Blurring of Social and Academic Engagement. (July 2013) - Lester, Jaime; Brown Leonard, Jeannie; Mathias, David
Transfer students are a distinct population. Their characteristics lead to a qualitatively different student experience. Drawing on interviews with a cross-sectional sample of transfer students at George Mason University (GMU), this study focused on the ways transfer students perceived their social and academic engagement, on the ways they engaged academically and socially at GMU, and on the ways in which their perceptions of engagement and their actual patterns of engagement affected their sense of belonging at GMU. Most notably, transfer students viewed social engagement in the context of family and community rather than college life. The findings have implications for how campuses support transfer students and question assumptions about some engagement theories.